Formas e função do discurso do outro no gênero monográfico - Pereira, Crígina Cibelle (2007)
The present work investigates related discourse in rewriting discursive practices, at monographic works specifically at the theoretical foundation section. Focalizing some discursive strategies of voice management (direct and indirect discourse and modalization voice) we detach the introduction way and function of cited discourse. To do so, it were analyzed eighteen monographic works: nine of them final graduation works and other nine specialization works seeing that each works belonging to the same student, in two different stages, in the period from 2003 in graduation conclusion to 2005 in the end of specialization course. The data reveal that the monographic writer/student emphasizes the use of direct discourse in graduation works while in specialization works there was an emphasis at indirect speech. The analysis the way they introduce cited discourse pointed out that writer/student in graduation course such as specialization student make meaningless constructions when they do not use discendi verbs, they demonstrate difficulties inarticulate citing discourse with cited discourse. In what is related to functions of cited discourse we verify that the student/writer, in both stages or levels give emphasis to the function maintain an assertion, indicating that other s discourse serve mainly as a resource of authority just because that this function reveals the absence of a dialog between student writing and cited discourse. In a general way, the forms of other s discourse claim a form of writing that is found starting from a sequence of cited discourse in what student/writer voice in graduation and specialization comes to text surface just few times, but most of the times, the student takes other s words as they were themselves, every time there is an overlap of author/source